1992
DOI: 10.1097/00000658-199204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy

Abstract: The impact of our evolving health care system on a commonly performed surgical procedure, cholecystectomy, was assessed in a county-subsidized and private university hospital setting. Although condition on admission, use of resources, and outcome were unchanged in the private setting between 1980 and 1988, significant differences were noted among the largely uninsured patients at the county facility during this same time interval. There was a significant increase in the acuity of illness among patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…The urban hospitals had a longer LOS, higher charges, and no differences in morbidity and mortality. This is in contrast to one study, which found that, although mortality rates were similar, the morbidity rate of cholecystectomy was higher in the large, private, university hospital than in the urban county hospital primarily serving the indigent population [24]. After we controlled for all other covariates in our analysis, neither size nor urban/rural location of the hospital was associated with an increased risk for complication or death.…”
Section: Discussioncontrasting
confidence: 93%
“…The urban hospitals had a longer LOS, higher charges, and no differences in morbidity and mortality. This is in contrast to one study, which found that, although mortality rates were similar, the morbidity rate of cholecystectomy was higher in the large, private, university hospital than in the urban county hospital primarily serving the indigent population [24]. After we controlled for all other covariates in our analysis, neither size nor urban/rural location of the hospital was associated with an increased risk for complication or death.…”
Section: Discussioncontrasting
confidence: 93%
“…Some of these problems are not unique in Australian health care delivery. A study of cholecystectomy in the United States revealed increased use of accident and emergency departments in county hospitals from 1980 to 1988 [15].…”
Section: Health Care Delivery In Australian Teaching Hospitalsmentioning
confidence: 99%